Intratubular light chain amyloidosis: a comprehensive analysis of disease spectrum and clinicopathological characteristics - Xiaoyu Wang; Yuxuan Yuan; Dan Zhou; Zhengyun Zhu; Yujie Wang; Feng Xu; Xiaodong Zhu; Mingchao Zhang; Fan Yang; Shaoshan Liang; Caihong Zeng (Clinical Kidney Journal, 2026)
Abstract Background The disease spectrum of intratubular light chain amyloidosis (AL) remains unkown. Methods Patients with intratubular AL from a single center were retrospectively analyzed and stratified into 3 groups: Group 1, complicated by extra-tubular amyloidosis; Group 2, complicated by light chain cast nephropathy (LCCN); and Group 3, isolated intratubular AL. Clinical features, pathological findings, treatment regimens, and renal prognosis were compared across the groups. Results The cohort (126 patients) was predominantly male (65.1%), with a mean age of 57 years and a high prevalence of the λ-light chain (78.6%). Group 1 was characterized by the lowest serum creatinine (Scr) and albumin, but the highest urinary protein and prevalence of systemic amyloidosis (all P < 0.05). Group 2 presented with higher Scr, prevalence of anemia and multiple myeloma (MM), elevated involved-to-uninvolved light chain ratio, and increased density of amyloid casts compared with Group 1 (all P < 0.05). Group 3 displayed similar hematological parameters and amyloid cast density as Group 1, with 1 patient displaying extrarenal amyloidosis. Overall, the hematological response rate was 54.3% and the renal remission rate was 26.4%. One patient in Group 3 progressed to MM. Group 2 had the highest incidence of end-stage renal disease (P < 0.05). Multivariate analysis identified Scr at biopsy as an independent predictor of renal prognosis. Conclusion Intratubular AL is frequently identified in patients with renal AL and LCCN, presenting with characteristics associated with these two disorders. Isolated intratubular AL could progress to MM or systemic amyloidosis, thereby necessitating vigilant clinical monitoring.